Food Effects, Pharmacokinetic Drug–Drug Interactions, and Clinical Optimization of Oral Anticancer Agents - Abdullah A. Assiri (Pharmaceutics, 2026)
Oral targeted therapies now constitute a substantial and growing proportion of anticancer drug therapy, shifting administration from the controlled intravenous setting to patient-managed oral therapy in the outpatient setting, where systemic exposure depends on factors that parenteral therapy largely bypasses. Food effects, gastric pH, first-pass metabolism, transporter activity, organ function, concomitant medications and adherence contribute to variability in exposure, and many oral anticancer agents have narrow therapeutic indices in which modest exposure changes carry clinical consequence. This review synthesizes the pharmacokinetic determinants of oral anticancer drug exposure across twenty-seven exemplar agents spanning the main mechanistic classes and translates them into actionable pharmacy practice. Its contribution is a cross-class agent-level comparison in which within-class divergences are made explicit, the integration of determinants usually reviewed separately, and an explicit statement of the evidence level behind every entry. We examine food effects, the interaction between acid-suppressive therapy and pH-dependent agents, the dominant role of cytochrome P450 3A4 and of the efflux transporters P-glycoprotein and breast cancer resistance protein, and the exposure–response relationships that motivate therapeutic drug monitoring, for which the evidence remains uneven and does not yet support routine use. We propose a structured framework for operationalizing these principles in daily practice.